An Analysis of the Inconsistency of Political Party Vote Outcomes in the 2024 General Election: A Case Study in Semarang City - Wasisto, Aryo Wasisto (Universitas Brawijaya, 2024)
Electoral inconsistencies in open-list proportional systems and model elections challenge discussion of factor complexity. This research investigates the factors influencing political party votes in the 2024 general election, with a focus on five polling stations in Semarang City. The purpose of this study is to determine the factors that drive the consistency and inconsistency of political party vote results in Semarang City. It is known that there are variations in vote acquisition among political parties in the DPR, provincial DPRD, and city DPRD elections, reflecting inconsistencies in voting behavior. This research highlights key factors such as the electoral system, local issues, negative or positive evaluations of party elites, and the practice of clientelism as the basis for why votes shift from one party to another. Finally, it provides insights into the researcher's overview at the polling station level, particularly in Semarang City in the context of the 2024 general election, and suggests the need for further combined research, such as expanding the scope of respondents and increasing the number of respondents.